1987
DOI: 10.1055/s-2008-1025650
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Oxygen Transport Before and After Short-Term Maximal Swimming in Dependence on Training Status

Abstract: Parameters of oxygen transport were determined in 12 national class swimmers of both sexes during a 6-week training phase. Training intensity was high at the beginning of the training period (60 km/week); at the end the intensity was reduced to 25 km/week. At the beginning, in the middle, and at the end of the training period maximal swim tests (3 X 50 m) were performed. At rest 2,3-diphosphoglycerate (2,3-DPG) concentration (+0.82 mmol/l RBC) and P50 values (+0.92 mmHg) were increased after the period of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…There is a significant positive relationship between the resting concentration of 2,3-DPG and VO 2max ( Remes et al, 1979 ; Mairbäurl et al, 1983 ; Czuba et al, 2009 ). It has been shown that 2,3-DPG concentration increases under the influence of exercise training ( Braumann et al, 1982 ; Hasibeder et al, 1987 ; Hespel et al, 1988 ; Schmidt et al, 1988 ), which is mainly due to the stimulation of erythropoiesis and an increase in the number of young RBC, which are characterized by higher metabolic activity and an increased level of 2,3-DPG ( Mairbäurl et al, 1983 ). It was also noted that in the subjects with a higher sport performance level, concentration of 2,3-DPG decreases after exercise, while it increases or is unchanged in subjects with lower fitness ( Thomson et al, 1974 ; Kuński and Sztobryn, 1976 ; Remes et al, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant positive relationship between the resting concentration of 2,3-DPG and VO 2max ( Remes et al, 1979 ; Mairbäurl et al, 1983 ; Czuba et al, 2009 ). It has been shown that 2,3-DPG concentration increases under the influence of exercise training ( Braumann et al, 1982 ; Hasibeder et al, 1987 ; Hespel et al, 1988 ; Schmidt et al, 1988 ), which is mainly due to the stimulation of erythropoiesis and an increase in the number of young RBC, which are characterized by higher metabolic activity and an increased level of 2,3-DPG ( Mairbäurl et al, 1983 ). It was also noted that in the subjects with a higher sport performance level, concentration of 2,3-DPG decreases after exercise, while it increases or is unchanged in subjects with lower fitness ( Thomson et al, 1974 ; Kuński and Sztobryn, 1976 ; Remes et al, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 2,3-DPG concentration may change in disease states (e.g., anemia, chronic obstructive lung disease, Parkinson’s disease, and cystic fibrosis; Alevizos and Stefanis, 1976 ; Acharya and Grimes, 1986 ; Illuchev et al, 1993 ; Böning et al, 2014 ) and under the influence of environmental conditions ( Koistinen et al, 2000 ; Savourey et al, 2004 ). It has been shown that the increase in 2,3-DPG level is a positive adaptation following endurance training lasting several weeks or months ( Böswart et al, 1980 ; Braumann et al, 1982 ; Hasibeder et al, 1987 ; Schmidt et al, 1988 ) and as a result of exposure to hypoxia ( Lenfant et al, 1968 ; Mairbäurl et al, 1986b ; Sutton et al, 1988 ). Acute hypoxic exposure causes hyperventilation and increases CO 2 removal, leading to respiratory alkalosis and an increase in blood pH ( Lühker et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy exercise causes destruction of red blood cells by mechanical stress e.g. in the heart, during passage through microvessels of contracting muscle or by the increased pressure on foot soles or hands depending on the kind of activity performed (41). This destruction removes mainly old less deformable red blood cells from circulation (61) and might act as an additional stimulus for erythropoiesis by a decrease in the 02-transport capacity.…”
Section: Erythropoiesis and Exercisementioning
confidence: 99%
“…Training has been associated with bleeding into the digestive tract, hemoglobinuria, myoglobinuria, hematuria, and iron loss into sweat (45,59,60). We have begun to study the problem and have found that unaccustomed exercise does increase the amount of "free iron," and that an increased susceptibility to oxidative stress is associated with such increased levels of iron (72).…”
Section: Ofher Nutrifional Factorsmentioning
confidence: 99%